Optimalisasi Peran Mahasiswa Pendamping Program Upsus Pajale Untuk Mempercepat Introduksi Teknologi Budidaya Jajar Legowo Super di Kabupaten Sijunjung - Siska Efendi (Universitas Sebelas Maret, 2020)
Title: Optimizing the Role of Assistance Student of Upsus Pajale Programs to Accelerate the Introduction of Cultivation Technology Jajar Legowo Super in Sijunjung RegencyThe Faculty of Agriculture of Andalas University is one of the government's partners in the successful implementation of Rice, Corn and Soybean (Upsus) Program at special province of West Sumatra. The implementation of Upsus Pajale in West Sumatra was found in eight districts and cities on 2017, one of which was Sijunjung Regency. Students and alumni participated as a companion in the implementation of several Upsus Pajale programs. In contrast to the implementation of Upsus Pajale in 2015 and 2016, in 2017, there were activities in applying technology in the work area of the accompanying students. The technology introduced by the field assistant lecturer together with the accompanying students, is the cultivation of Jajar Legowo super. The application of this technology was implemented in three sub-districts in Sijunjung Regency, namely Sijunjung, Tanjung Gadang and Kamang Baru. The activity was carried out in the form of a demonstration plot on the partner farmer's group's land. The technology of jajar legowo super has been successfully introduced to partner farmer groups, which is marked by increased production. The results showed that there was an increase in rice productivity using the Jajar Legowo Super method up to 4.6 tons / ha to 5.2 tons / ha than the conventional method of only 1.7-2 tons / ha.